Survival Benefits of Anti-PD-1 Therapy in Combination With Radiotherapy in Chinese Melanoma Patients With Brain Metastasis - Wu, Shuang; Yuan, Chuanping; Chen, Lei; Guo, Lanlan; Chen, Yong; Peng, Zhenwei; Lu, Lixia (Frontiers in Oncology, 2021)
Limited data reported the synergistic anti-tumor effect of anti-PD-1 (programmed death 1) therapy and radiotherapy on melanoma BM (brain metastasis). And the efficacy in the Chinese population is unclear. This study aimed to evaluate the efficacy of anti-PD-1 therapy and radiotherapy in Chinese melanoma patients with BM. We retrospectively reviewed 96 consecutive melanoma patients with BM treated at Sun Yat-Sen University Cancer Center. Patient demographics, BM characteristics and treatment details were carefully collected. The intracranial PFS (progression free survival) and OS (overall survival) were estimated using the Kaplan-Meier method. Twenty-five patients were treated with anti-PD-1 therapy and radiotherapy. Eighteen (72.0%) patients had SBRT (stereotactic body radiation therapy) or SRS (stereotactic radiosurgery) for BM, 1 (4.0%) patient had WBRT (whole brain radiation therapy), 6 (24.0%) patients had SBRT/SRS and WBRT. The median treatment period of anti-PD-1 therapy was 10.77 months. Objective intracranial response was observed in 15 (60%) patients, and 5 (20%) patients achieved CR (complete response). After a median follow-up of 16 months, 11 (44%) patients experienced intracranial PD (progressive disease), and 15 (60%) patients died. The median intracranial PFS and OS were 10.73 months (range, 1.67- 38.83 months) and 15.87 months (range, 2.47- 41.50 months), respectively. The 1-year intracranial PFS and OS were 61.9% (95% CI, 44.1-86.9%) and 62.5% (95%CI, 45.8-85.2%), respectively. Patients with BM can benefit from a combination of anti-PD-1 therapy and radiotherapy. It merits further investigation in melanoma patients with BM.